Comparative Analysis of a New Hybrid EDOF-Multifocal Diffractive Intraocular Lens with a Trifocal Diffractive Intraocular Lens. Issue 5 (September 2022) - Ozturkmen, Cem; Kesim, Cem; Gunel Karadeniz, Pinar; Sahin, Afsun
Purpose: To compare visual acuity, defocus curve and visual quality of life performances of a new hybrid refractive-diffractive intraocular lens (IOL) and a trifocal diffractive IOL. Methods: Patients who underwent cataract surgery with bilateral implantation of ZFR00V or TFNT00 IOLs were enrolled in this study. The main outcomes were defined as uncorrected distant, intermediate and near visual acuities (UDVA, UIVA and UNVA, respectively), defocus curve and VF-14 questionnaire aimed for visual performance. Results: Fifty patients, of whom 30 had bilateral ZFR00V implantation, were enrolled in the study. Patients with ZFR00V had significantly better UIVA than patients with TFNT00 (0.05 ± 0.03 vs. 0.07 ± 0.04 logMAR, P = 0.02). Defocus curve showed significantly higher visual acuity in intermediate range for ZFR00V IOL between −1.00 and −1.50 dioptres (all P < 0.05). All patients had good visual performance with mean VF-14 scores above 3 points with no significant difference between two IOL models. Spectacle independence was 100% for both distant and near vision in both group of patients. Conclusion: Bilateral implantation of ZFR00V in cataract patients shows better intermediate visual acuity scores and similar daily visual performance when compared with trifocal TFNT00 IOL.